PEMANFAATAN PEMASARAN DIGITAL PADA KOMODITAS HORTIKULTURA UNTUK MENINGKATKAN PENDAPATAN PETANI DI KABUPATEN HALMAHERA SELATAN - Fatmawati Kaddas ,; Haris Mahmud ,; Khairun Annisa ,; Mardiyani Sidayat ,; Mila Fatmawati ,; Natal Basuki ,; Nurdiyanawati Djumadil ,; Nursamsi, Nursamsi; Syahroni, Syahroni; Herman Darwis , (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Digital marketing of horticultural commodities can improve the economy and the welfare of the community, especially farmers. However, most farmers in South Halmahera Regency still rely on traditional marketing methods, such as direct sales to the local market or through middlemen. Therefore, service activities need to be held and packaged in a form of trainings, including training on the importance of digital marketing and also mentoring activities. The training participants in this activity were horticultural farmers who looked very enthusiastic about the training material provided, this can be seen from the beginning to the end of the activity all participants followed well. The expected output target is to increase the skills of horticultural farmers in South Halmahera Regency about digital technology in marketing their agricultural products and provide opportunities to increase the income of horticultural farmers in South Halmahera Regency